2007
DOI: 10.2214/ajr.07.2173
|View full text |Cite
|
Sign up to set email alerts
|

Sonographically Guided Percutaneous Catheter Drainage Versus Needle Aspiration in the Management of Pyogenic Liver Abscess

Abstract: PCD is more effective than percutaneous needle aspiration in the management of liver abscess. Percutaneous needle aspiration can be used as a valid alternative for simple abscesses 50 mm in diameter or smaller.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
158
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(174 citation statements)
references
References 18 publications
5
158
0
9
Order By: Relevance
“…A study reported a frequency of 85%-90% successful treatment with percutaneous abscess drainage in children which was reported to be similar to that in adults [8]. Zerem et al opined that percutaneous catheter drainage (PCD) is more effective than percutaneous needle aspiration in the management of liver abscess and that percutaneous needle aspiration should be used as a valid alternative for simple abscesses 50mm in diameter or smaller [9]. However other authors' opinion differed since multi-loculated abscesses have been drained using direct needle puncture [13].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A study reported a frequency of 85%-90% successful treatment with percutaneous abscess drainage in children which was reported to be similar to that in adults [8]. Zerem et al opined that percutaneous catheter drainage (PCD) is more effective than percutaneous needle aspiration in the management of liver abscess and that percutaneous needle aspiration should be used as a valid alternative for simple abscesses 50mm in diameter or smaller [9]. However other authors' opinion differed since multi-loculated abscesses have been drained using direct needle puncture [13].…”
Section: Discussionmentioning
confidence: 89%
“…In the past, management of abscess was surgically performed [9]. PD has replaced open surgical drainage in most situations, except when the abscess is very large, multi-septated and in cases where PD failed, sepsis is unabated, and when PD is impossible due to interposed structures such as overlying bowels [3,8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, USG guided percutaneous aspiration was performed in abscesses less than 150 cc in 18% of patients. Ramani Repeated aspirations are necessary for large abscesses as described by Georgio et al 5,20,21 In these cases, chances of infection and trauma of repeated aspirations can be nulled by catheter drainage. Moreover, single aspiration runs the risk of leakage of pus from punctured and inadequately decompressed abscess, with peritoneal contamination warranting surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicated the benefits of percutaneous drainage versus needle aspiration for larger abscesses including a prospective randomized control study. [2][3][4] A review of US data by Levin et al showed a significant decline in surgical management of hepatic abscesses and an increase in percutaneous drainage. 5 No randomized controlled studies were found examining percutaneous versus surgical drainage.…”
Section: Related Literaturementioning
confidence: 99%